The Effect of Perceived Product Quality, Perceived Price, and Celebrity Credibility on the Intention to Repurchase Nivea Hand and Body Lotion in Bandung - Reni Indriyani; Faizal Fardhani Sigarlaki (LP2M IAIN Palopo, 2026)
This study aims to analyze the influence of perceived product quality, perceived price, and celebrity credibility on the intention to repurchase NIVEA Hand and Body Lotion in Bandung. This study employed a survey method involving respondents who had previously purchased and used NIVEA Hand and Body Lotion in Bandung. The sampling technique used purposive sampling with a sample size of 160 respondents. Data analysis was conducted using multiple linear regression analysis with the aid of SPSS version 25 software. The results indicate that perceptions of product quality, price, and celebrity credibility fall into the “good” category. Individually, perceptions of product quality, price, and celebrity credibility have a positive and significant effect on repurchase intention. Simultaneously, these three variables also have a positive and significant effect on the repurchase intention for NIVEA Hand and Body Lotion in Bandung. These findings indicate that improving product quality, setting appropriate prices, and using credible celebrities can increase consumers’ willingness to repurchase. The results of this study are expected to serve as a basis for companies in developing effective marketing strategies to enhance consumer loyalty and brand competitiveness.